中国股票市场投资风险分析 = The risk analysis of investment in China's Stock Market - 顾汉德 Gu, Hande (2008)
This study focus on risk analysis of investment in China's Stock Market. The risk in the China's market has been caused by the following factors: the irregular behavior of the relevant government authorities; instabilities of stock market-related policies; the poor performance of the listed companies; the poor investment considerations from investors; lack of investment funds; the poor management of listed companies; the distorted behavior of the stock companies. All these factors are originated from the underdeveloped capital market in China. But these factors, in return, substantially constrained the development of the capital and stock market in China. This study also studys the measures of minimizing investment risks in the distorted China's stock market.